Práticas de manejo realizadas na criação de bezerras em aleitamento em propriedades leiteiras do município de Dois Vizinhos-PR - Schonarth, Caroline (2023)
Dairy farming is an essential activity for the economy of the country, ensuring employment and income, both in the countryside and in the cities. Good practices in raising dairy calves for suckling are extremely important for the success of dairy farming. However, many producers still neglect this phase because they do not immediately obtain a return on investment. The objective of this work carried out a data collection about management practices in suckling dairy calves, in fifteen dairy farms, with Compost Barn system, in the municipality of Dois Vizinhos, PR. Data were collected through a semi-structured interview with sixteen multiple choice questions and eleven open questions through a visit to the property. The dates were analyzed through simple descriptive statistics and one analysis of regression. 66.67% of the producers carry out weaning gradually and 73.33% provide, during the lactation period, 4 to 6 liters per day. In addition, 60% of respondents already use a concentrate with a crude protein content between 20 and 24%. It was observed that management practices in the creation of dairy calves in the municipality of Dois Vizinhos, PR, in a Compost Barn system, are carried out adequately by most producers, however, the presence of technical assistance in these properties is still necessary to improve the management of antenatal cows and suckling calves.